STRATEGI PENINGKATAN KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN DOMPU (Studi Empiris Terhadap Hasil Audit Badan Pemeriksa Keuangan R.I tahun 2006-2010) - , Samsudin; , Dr. Wahyu Widayat, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In local government, the inspection of local financial statement is carried out by the Financial Inspection Board. The objective is to enhance trust among the users of financial statement, in this case local financial statement. The statement should comply with standards, including relevant and reliable in nature. It shows that the data of financial statement was varified and can be regarded as fair. The main objective of the study are to identify strengths, weaknesses, opportunities, and threats in the enhancement of financial statement quality in Dompu regency, and to analyze strategies that should be prioritized in the enhancement of financial statement quality based on findings of the SWOT analysis. The study was conducted using a qualitative method in terms of analyzing strengths, weaknesses, opportunities, and threats in the enhancement of financial statement in Dompu Regency. Data used were primary and secondary data. The former was directly acquired from location of the study by using questionnaires and observation. Meanwhile, secondary data were indirectly acquired from related documents and regulations associated with the problems. The data collected were analyzed using a qualitative technique. Result of the study shows that Dompu Regency undergo problems related to relatively severe local financial statement, so result of the inspection done by the Financial Inspection Board indicates disclaimer opinion constitutively from 2006 to 2010. The government of Dompu Regency had Threats that should be immediately changed into opportunities as well as weaknesses that should also be changed into Strengths in the enhancement of local financial statement quality. The highest score among the dimensions of SWOT in the enhancement of local financial statement quality in Dompu Regency was threats (1,064), followed by weaknesses (1,046), opportunities (1,061), and strenghts (913). Based in such findings, the Local Government of Dompu Rgeency should emphasize dimensions of threats and weaknesses with highest scores as the basis of formulating the strategies for enhancing the quality of local financial statement. Among the main priorities that should be done are to improve the procedures for the allocation and reporting the local financial statement to reduce vulnerability in the misuse of authority, as well as to increase the number and quality of prevailing regulations to reduce the tendency of misuse due to no obvious legal basis.